Dirāsah Tahlīliyah Limanhaj Kitāb Ta’lim Allughah Al’arabiah Lilshafi Al ūla Altsanawī Biwizārah Alsyu`ūn Aldīniyah Al Indūnīsiyah ām 2020 alā Daw' Kitāb Ida'āt Limu’alimī Allughah Al’arabiah Lighayri Alnātiqīn Bihā - Musdalifa; Kristiana (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
This study aims to know the extent of the good curriculum standard in the Arabic language teaching book of the Indonesian Ministry of Religious Affairs in 2020 for the first secondary grade by referring to the book “Idoat Limuallimil Luqoh Al-Arabiyyah Li Goiri An-Natiqiina Biha